SYSTEMATIC LITERATURE REVIEW ON EFFECTIVE TEACHER COMMUNICATION STRATEGIES - Thahira, Afifa; Fitri, Indah Nabila; Mahdum, Mahdum; Azhar, Fadly; Dahnilsyah, Dahnilsyah (STKIP Pesisir Selatan, 2025)
This study aims to identify and compare effective communication strategies used by educators in two distinct educational contexts: teacher–student communication in schools and lecturer–student communication in higher education. Employing a Systematic Literature Review (SLR) approach, this study analyzed 15 relevant articles published between 2015 and 2025 that were selected from several reputable databases, including Scopus, ERIC, Google Scholar (SINTA 2–4), and various international journals. The selection process involved systematic screening, inclusion criteria, and quality assessment to ensure the relevance and rigor of the reviewed studies. The findings reveal several similarities in the communication strategies applied across both educational levels, particularly in the use of clear instructional messages, effective feedback mechanisms, nonverbal communication, and the development of positive interpersonal relationships between educators and learners. However, notable differences were also identified. At the school level, communication strategies tend to focus on instructional clarity, structured interaction patterns, scaffolding, classroom management, and emotional support for students. In contrast, communication at the university level emphasizes facilitating in-depth discussions, fostering academic autonomy, applying teacher immediacy, providing academic consultation, and strengthening students’ motivation.